Schaum's Signals and Systems Problem 1.2 : Discrete-time signal transformations using MATLAB - Berry, Carlotta (McGraw-Hill's AccessEngineering., 2020)
This video will describe how to use MATLAB to perform signal transformations on discrete-time signals.